1993
DOI: 10.1002/cber.19931260215
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the Chemistry of Boron, 214. Synthesis and Reaction Chemistry of Aminophosphanylboranes

Abstract: The formation of phosphanylboranes, R2P -BX2, from hydrogen or hydrogen halide elimination reactions between appropriate phosphane and borane reagents was examined intently for a number of These studies led to the isolation and partial characterization of several molecular ring compounds (RzPBX2), (n = 2, 3) as well as oligomeric species. Some of this chemistry has recently been revisited and extended in order to obtain monomeric boraphosphene species that contain a -P = B -double bond and to define new classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 66 publications
4
22
0
Order By: Relevance
“…Compound 7 was not isolated and purified; however, the 31 P NMR spectrum of the system prior to the addition of t BuLi shows a resonance for the known compound 5, δ 164, 10 and a resonance at δ -1.0, which is in the region expected for a bicyclic cage fragment. The proposed process is outlined in Scheme 1.…”
mentioning
confidence: 96%
“…Compound 7 was not isolated and purified; however, the 31 P NMR spectrum of the system prior to the addition of t BuLi shows a resonance for the known compound 5, δ 164, 10 and a resonance at δ -1.0, which is in the region expected for a bicyclic cage fragment. The proposed process is outlined in Scheme 1.…”
mentioning
confidence: 96%
“…Two of the most puckered members of this family, [HP-B(NR 2 )] 3 , appear in two different conformations, a 38% trigonal prismatic boat for R = i Pr, 71 and a 29% octahedral chair for R = SiMe 3 . 72 The resulting loss of aromaticity in the former has provided an explanation for the long B-P bond lengths compared to those in similar rings. An isoelectronic compound intimately related to this family, a diazatetraborinin with a para-B 4 N 2 core, is a nearly perfectly planar hexagonal six π electron aromatic molecule 2.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The chemistry of diphosphinoboranes has been explored to a lesser extent than that of other P–B systems ( Chart 1 B). Most synthesis attempts have been made by Nöth et al 19 − 21 Recently, we vastly expanded the chemistry of these compounds, not only by the synthesis and isolation of several new diphosphinoboranes 22 but also by revealing their potential in the activation of small molecules. 23 Our preliminary research on the reactivity of selected diphosphinoboranes revealed that these species react with isocyanates, CO 2 , and H 2 .…”
Section: Introductionmentioning
confidence: 99%